Design Strategies for Adaptive Residential Houses in Flood-Prone Areas: A Case Study of RT. 28, Loa Janan Ulu Village, Kutai Kartanegara - M. Syafrudin; Robert Riyanto Widjaja; Antonius Adriyanto (International Journal Labs, 2026)
The phenomenon of floods loaded with mud sediment due to rainfall and massive mining activities upstream are a serious threat to settlements in RT. 28, Loa Janan Ulu Village, Kutai Kartanegara. Therefore, this study aims to formulate a strategy for designing adaptive residential houses that are resilient to sediment-laden floods, as a practical guide for the community and a reference for technical standards for policy makers. The research framework combined social behaviour theories such as the tendency to stay at home (In-situ Coping) and Place Attachment with an Adaptive Architecture approach that includes the concept of Living with Water, vertical zoning arrangements, and material resilience (Material Recoverability). The research was applied through four systematic stages: (1) identification of natural traces and flood impacts to determine the parameters of critical elevation of floods (Hmax) and sediment types; (2) mapping of residents' adaptation behaviour patterns independently; (3) architectural synthesis using adaptability matrix; and (4) formulation of final design strategies. The results of the study show that the relevant adaptive design strategy is to revitalize the local wisdom of the vernacular architecture of Rumah Kutai through three main technical principles: the application of strict vertical zoning to separate the Wet Zone in the lower area and the Dry Zone on the upper floor; the use of low-porosity washable materials such as hydrophobic exposed concrete and WPC composites; and the application of a hybrid stage structure that allows water to flow freely under the building to reduce hydrodynamic pressure loads.